DATA-DRIVEN PUBLIC RELATIONS STRATEGY IN MADRASAHS: A NEURAL NARRATIVE INTELLIGENCE APPROACH - Kusumawati, Ida; Khofsah, Siti; Jannatul Firdausiyah, Rifka; Najiburrohman, Najiburrohman; Baharun, Hasan (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2026)
Public opinion today evolves so rapidly that it is impossible to calculate time. If it is not managed correctly and ethically, the impact will be significant on madrasas, the environment, and even the community's mental health. This research examines how public relations strategies manage and understand public opinion using the Neural Narrative Intelligence model. The method used in this study is a qualitative-descriptive approach, with a literature review, and collects and analyzes various sources on public opinion, public relations, and public relations strategy. Research objectives. This produces public relations, or a madrasah follows the times; ethics respond to public opinion; the madrasa's reputation remains enduring, even increasing, and public trust becomes stronger. The study shows that public relations strategies can formulate proactive, effective, and relevant strategies and provide a description of how to pattern public opinion using Neural Narrative Intelligence. Findings. This is to explain that Neural Narrative Intelligence is an important thing for public relations in the educational environment. This study contributes to Islamic education management by proposing an AI-based narrative intelligence framework for proactive and ethical public relations governance in madrasahs.